SPACE ARRANJEMENTS FOR BEANS IN DIRECT SOWING - KRINSKI, Silvio Alexsandro (Scientia Agraria, 2002)
A field trial was carried out at Colégio Agrícola Estadual Getúlio Vargas (Palmeira, PR, Brazil) from November, 08th 2000 till February, 02nd 2001. Morphological characteristics, yield components and yield was analyzed in order to determine the most adequated spatial arrangement for dry bean in no-tillage system. The variety used was FT BIONOBRE. Row widths varied, while the population of 270,000 plants.ha-1 was maintained constant. The experimental design used to analyze yield, yield components and harvest index was a randomized complete block, with four treatments (0.30 m, 0.40 m, 0.50 m and 0.60 m) and eight replications. A randomized complete block for width row, with developmental stages R5, R6, R7, R8 and R9, split plot on it, was used to evaluate other characteristics that occur during the development of the crop. Plots were formed by ten rows with 5.0 m length. Population was standardized by thinning in the four width rows, in which remained about 8.1; 10.8; 13.5; and 16.2 plants.m-1. Spatial arrangements of plants affected morphological characteristics of dry bean. Lower results of leaf area and dry matter of different parts of plants were observed in the lowest row width. These characteristics contributed to reduce the mean number of pods per plant, which was the only yield component affected by spatial arrangement of plants. However, the lowest row width, in which the plants were distributed equidistantly, contributed to occurrence of more efficient plants. In these plants, more carbohydrates were translocated to grains. Therefore, harvest index and yield was increased.